2022
DOI: 10.1002/pc.27157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the subsidiary materials of the manufacturing process on the microstructure of the composite laminate

Abstract: Composite specimens with resin contents of 33.5%, 35.4%, and 35.9%, respectively, were manufactured by controlling the type of subsidiary material used in the bagging process for a composite material having the same composition.The effect of controlling the resin content on the microstructure and mechanical properties of composite specimens was investigated. The flow of resin and air during the cure process was inferred and explained by connecting it with the microstructure. Specifically, the behavior of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In previous studies, voids were observed in the area where subsidiary materials were laminated, not on the first layered lay-up mold surface, and it was reported that these results varied according to the resin and air flow, which depended on the selection of subsidiary materials. 30 Except in Figure 5a, it was confirmed that voids were formed in the area where subsidiary materials were lay-up. Under the influence of the bagging film in the bagging process, the internal air flow continuously flows in the vacuum direction and is maintained until the cure process.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…In previous studies, voids were observed in the area where subsidiary materials were laminated, not on the first layered lay-up mold surface, and it was reported that these results varied according to the resin and air flow, which depended on the selection of subsidiary materials. 30 Except in Figure 5a, it was confirmed that voids were formed in the area where subsidiary materials were lay-up. Under the influence of the bagging film in the bagging process, the internal air flow continuously flows in the vacuum direction and is maintained until the cure process.…”
Section: Resultsmentioning
confidence: 85%
“…The result of the test is the average of the specimens tested under each condition. Checking the test results of the tensile laminate specimens in Table 3, the strength values of Case 1, Case 2, 30 Case 3, 30 and Case 4 30 were 514.2 MPa, 539 MPa, 534 MPa, and 536 MPa, respectively, and the young’s modulus value was 26.4 GPa, 25.9 GPa, 25.3 GPa, and 25.2 GPa, respectively. The mechanical strength property of the composite laminate specimen has a value between the reinforcement having high strength and Young’s modulus and the matrix property having low strength and Young’s modulus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation